Femoropopliteal In-stent Restenosis Repair: Midterm Outcomes After Paclitaxel Eluting Balloon Use (PLAISIR Trial). (January 2017) - Bague, N.; Julia, P.; Sauguet, A.; Pernès, J.M.; Chatelard, P.; Garbé, J.F.; Penillon, S.; Cardon, J.M.; Commeau, P.; Planché, O.; Guyomarch, B.; Gouëffic, Y.
Abstract : Objective: The aim was to assess 18 month outcomes of the paclitaxel eluting balloon (PEB) in patients with femoropopliteal (FP) in-stent restenosis (ISR). Methods: In a national prospective and multicentre cohort study, symptomatic patients with femoropopliteal in-stent restenosis were included from January 2012 to June 2013. Patients were treated by paclitaxel eluting balloon angioplasty (In Pact Admiral, Medtronic, Santa Rosa, CA, USA). Clinical and duplex scan follow-up evaluations were performed at 1, 3, 6, 9, 12, and 18 months. The primary endpoint was freedom from target lesion revascularisation (TLR) at 12 months. Secondary endpoints were major adverse cardiovascular events (MACE), Target extremity revascularisation (TER), primary and secondary sustained clinical improvement, recurrent restenosis rate, primary and secondary patency, quality of life assessed by EQ-5D questionnaire, technical success, clinical success, and length of stay Results: A total of 53 patients were enrolled. After a blinded review, 10 patients were defined as protocol violation because restenosis occurred more than 2 years after stent implantation. Procedures were performed in 55 limbs, 48 (87%) for claudication and 7 (13%) for critical limb ischaemia. The mean diameter and length of PEB were 6 ± 0.57 mm and 86 mm ± 32 mm, follow-up was 17 months (range 1–19). At 1 year, the survival rate was 96 ± 2.7% and freedom from TLR and TER were 90.2 ± 4.2% and 85 ± 5%, respectively. Sustained primary and secondary clinical improvements were 78.6 ± 5.7% and 92.0 ± 3.8%, respectively. At 1 year, the primary patency rate was 83.7 ± 5.0%. Prior to the procedure, the mean EQ-5D score was 66 ± 14 and 74 ± 16 at 1 year ( p  = .10). Two patients died during follow-up; one patient died 33 days after the procedure because of limb ischaemia. Conclusion: PEB for the treatment of FP ISR is associated with a low rate of re-interventions and restenosis. Clinical improvement is maintained at 18 months.